Pathological features in perinatal autopsy and its relation with clinical and antenatal sonography findings - P., Aswathy; Pothen, Lillykutty; Thambi, Renu; S., Sankar (International Journal of Research in Medical Sciences, 2022)
Background: Perinatal mortality is considered as a yardstick of obstetric and maternal care before and around the time of death. Perinatal autopsy is an inevitable procedure which helps to ascertain the cause of death, identify rare diseases, supplements clinical diagnosis and provide risk estimates for future pregnancies. The aim of the study was to describe the pathological features in perinatal autopsy specimens and to compare the pathological features with clinical and antenatal sonography findings. Methods: A descriptive study was conducted among 43 perinatal autopsy cases. A thorough perinatal autopsy was done. Detailed maternal medical and obstetric history including the laboratory and USG findings were collected. Collected data analysed using Statistical package for social sciences (SPSS) software. Results: The results were grouped into fetal, maternal and placental findings. Congenital anomalies were detected in 20% cases. That included gastrochisis, ebstein anomaly, isolated dextrocardia, hypoplastic left heart syndrome, cleft lip and palate, prune belly syndrome, club foot. Placenta findings observed were chorioamnionitis, placental thrombotic vasculopathy and placental findings in COVID-19 positive cases. The most common maternal comorbidity was hypertension (20.9%). Perinatal mortality was high in those cases with past history of abortions and history of infertility treatment. Full agreement between perinatal autopsy and antenatal USG findings was detected in 36.36% cases. Additional anomalies detected on autopsy was 54.54%. Conclusions: A thorough clinical history, prenatal ultrasonography and perinatal autopsy features could be described in detail in all the cases. Comparison of finding at autopsy with antenatal ultrasonography finding indicate that ultrasonography finding have only a reasonable value in assessing fetal status. Advanced radiology techniques could be maximum helpful.